2010
DOI: 10.1016/j.psychres.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Attention to novel and target stimuli in trauma survivors

Abstract: Trauma and its consequences can have lasting biological and cognitive effects on those who experience them. This study investigated the extent to which trauma, PTSD, and dissociation influenced attention to basic auditory stimuli in a sample of military cadets. After filling out a series of psychometric questionnaires, twenty-seven male military cadets varying in their trauma history participated in the "novelty" oddball task in which participants were asked to count high pitched tones while ignoring other aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 48 publications
4
32
0
Order By: Relevance
“…In view of these and the present findings attentional bias following trauma may not be as clear-cut as previously assumed but a more complex phenomenon with its components being related to different posttraumatic (comorbid) symptomatology (see also Kimble et al (2010)). Thus, after trauma exposure different components of attentional bias may contribute to the development of or become maintaining factors for qualitatively or quantitatively different posttraumatic pathologies (see also Shipherd and Salters-Pedneault (2008), Pineles et al (2007Pineles et al ( , 2009) for further discussion).…”
Section: Summary Of Resultssupporting
confidence: 59%
“…In view of these and the present findings attentional bias following trauma may not be as clear-cut as previously assumed but a more complex phenomenon with its components being related to different posttraumatic (comorbid) symptomatology (see also Kimble et al (2010)). Thus, after trauma exposure different components of attentional bias may contribute to the development of or become maintaining factors for qualitatively or quantitatively different posttraumatic pathologies (see also Shipherd and Salters-Pedneault (2008), Pineles et al (2007Pineles et al ( , 2009) for further discussion).…”
Section: Summary Of Resultssupporting
confidence: 59%
“…Likewise, another study that investigated never-treated, comorbid-free PTSD patients following the Tokyo subway sarin attack reported a negative correlation between P300 and avoidance/numbing (Araki et al, 2005). However, some oddball studies did not find significant correlations between P300 and PTSS (Kimble et al, 2010;Lamprecht et al, 2004;Neylan et al, 2003;Veltmeyer et al, 2005), which demonstrates the conflicting findings regarding the relationship between PTSS and P300 obtained using this paradigm.…”
Section: Felminghan Et Al (2002) Studied Non-sexual Assault and Motomentioning
confidence: 97%
“…Other auditory tasks, such as the auditory oddball task, though numerous, have yielded a number of dimensionally negative data regarding ERPs and PTSS severity (Ge et al, 2011;Holstein et al, 2010;Kimble et al, 2010;Lamprecht et al, 2004;Neylan et al, 2003;Veltmeyer et al, 2005). Among the auditory oddball studies, the exception was a current source analysis of the P300 component that observed a significant inverse correlation between PTSS and the P300 current source density in the posterior cingulate gyrus (Bae et al, 2011).…”
Section: Erp Studiesmentioning
confidence: 99%
“…A decrease in late event-related potentials (p300) during conversion and dissociative episodes has been found, and its reduction disappeared after recovery (Rief et al, 1998;Kimble et al, 2010). The opposite phenomenon has been objectified in individuals presenting high interoceptive awareness (Pollatos et al, 2005).…”
Section: Neurobiological Bases Of Conversion Disordermentioning
confidence: 99%